Pengaruh Alih Fungsi Lahan Terhadap Ketahanan Pangan, Lingkungan, dan Keberlanjutan Pertanian di Kabupaten Sleman - Putri, Indriana Diani; Martanto, Rochmat; Junarto, Rohmat (Sekolah Tinggi Pertanahan Nasional, 2024)
Land conversion in Sleman Regency is on the rise, driven by population growth, economic development, and urbanization, posing risks to food security, farmer welfare, and environmental sustainability. This study seeks to assess the effects of land conversion and effective management strategies to ensure sustainable food security. The employed methods consist of image interpretation, observation, interviews, and document analysis, complemented by quantitative analysis to assess changes in land area and distribution patterns of land conversion. The research findings indicate that land conversion in Sleman exhibits a clustered pattern, leading to a decrease in agricultural land area. This reduction impacts food security, environmental quality, and biodiversity while simultaneously increasing land value and the cost of living. Food security zoning has been categorized into three distinct types: convertible land zones, characterized by low food security, located in Depok, Ngaglik, and Mlati; buffer land zones found in Godean, Ngemplak, and Berbah; and land designated for sustainable agriculture, situated in Turi, Pakem, Cangkringan, Tempel, Kalasan, Prambanan, Seyegan, Minggir, and Moyudan. Strategies for controlling land conversion encompass spatial planning regulations, LP2B protection, cross-sector collaboration, community participation, and regular monitoring and evaluation by pertinent agencies. Land conversion adversely affects food security and environmental conditions in Sleman. Effective control strategies are essential for achieving a balance among development, environmental sustainability, and community welfare. Alih fungsi lahan di Kabupaten Sleman meningkat akibat pertumbuhan penduduk, perkembangan ekonomi, dan urbanisasi, yang mengancam ketahanan pangan, kesejahteraan petani, serta keberlanjutan lingkungan. Penelitian ini bertujuan mengidentifikasi dampak alih fungsi lahan dan strategi pengendalian yang tepat untuk mencapai ketahanan pangan berkelanjutan. Metode yang digunakan meliputi interpretasi citra, observasi, wawancara, dan studi dokumen, dengan analisis kuantitatif untuk mengukur perubahan luas lahan dan pola persebaran alih fungsi lahan. Hasil penelitian menunjukkan alih fungsi lahan di Sleman berpola mengelompok, mengakibatkan pengurangan luas lahan pertanian yang mempengaruhi ketahanan pangan, kualitas lingkungan, keanekaragaman hayati, serta peningkatan nilai tanah dan biaya hidup. Zonasi ketahanan pangan diidentifikasi menjadi tiga: Zona Convertible Land (ketahanan pangan rendah) di Depok, Ngaglik, dan Mlati; Zona Buffer Land di Godean, Ngemplak, dan Berbah; serta Zona Land For Sustainable (pertanian berkelanjutan) di Turi, Pakem, Cangkringan, Tempel, Kalasan, Prambanan, Seyegan, Minggir, dan Moyudan. Strategi pengendalian alih fungsi lahan meliputi peraturan tata ruang, perlindungan LP2B, kolaborasi lintas sektor, partisipasi masyarakat, serta pengawasan dan evaluasi rutin oleh instansi terkait. Alih fungsi lahan berdampak negatif pada ketahanan pangan dan lingkungan di Sleman. Diperlukan strategi pengendalian yang tepat untuk menjaga keseimbangan antara pembangunan dan kelestarian lingkungan serta kesejahteraan masyarakat.